Improving Student Life Skills Through the Ma Plus Skills Program at MAN 4 Kediri - mahmudi Mahmudi; Muhammad Arif Khoiruddin (Journal of Humanities Research Sustainability, 2024)
Background. This research is motivated by the importance of the relevance of education to the needs of skills in the world of work, especially for madrasas which are often considered only oriented to the needs of the ukhrawi. Purpose. The purpose of the study was to analyze the planning, implementation, and evaluation of the skills program at MAN 4 Kediri as an effort to improve students' life skills. Method. The research method uses a qualitative approach with data collection techniques through observation, interviews, and documentation. Results. The results showed that the planning of the skills program was carried out by forming a special team that collaborated with the head of curriculum in preparing learning tools according to KMA number 184 of 2019. Learning implementation involves competent educators and gets support from the madrasah head, with an allocation of 6 hours per week. Evaluation is carried out by teachers, deputy heads and madrasah heads, focusing on the implementation of activities and the achievement of KKM, and followed up according to the problems that arise.  Conclusion. In conclusion, the series of planning, implementation, and evaluation processes of the skills program at MAN 4 Kediri are in accordance with the guidelines for implementing MA Plus Skills, although routine and detailed supervision by the madrasah head is still needed for the performance of teaching staff.